Determinan Biaya Utang Perusahaan Otomotif dan Produk Komponen Tahun 2014-2019 - Destia Rahmatu Jannah; Dewi Purwanti (Seminar Nasional Official Statistics, 2021)
Indonesia is the largest automotive market in ASEAN, this is indicated by the highest car and motorcycle sales in ASEAN for the 2014-2019 period. In addition, exports of cars and motorcycles in Indonesia have an increasing trend. This causes manufacturing companies in the automotive and component product sub-sectors to experience rapid asset growth every year, because each company continues to develop its production. Every company in developing its business requires not only internal funding but also external funding by making debt loans through creditors. Companies prefer debt because it has a relatively small cost compared to issuing new shares even though the risks faced are greater. Borrowing debt can incur cost of debt for corporate. This study aims to analyze the cost of debt and examine the determinants of the cost of debt of manufacturing companies in the automotive and component products sub-sector listed on the IDX during the period 2014 to 2019. The method used is a fixed effect model with cross sectional weight. Based on the results of the study, it can be concluded that the debt to equity ratio has a positive and significant effect on the cost of debt. While the variables of return on assets, firm size, and current ratio have a negative and significant effect on the cost of debt.